The contribution of Italian migrant women in the New World to health and safety at work - Salerno, Silvana (La Medicina del Lavoro, 2018)
Background: Many Italian migrant women left Italy for the United States of America (USA) in the years 1881-1932. In the USA they could only find poor jobs such as home work or unskilled jobs in the developing American manufacturing industries. Objectives: Analysis of the contribution of Italian migrant women to the improvement of working conditions in the USA. Methods: Five case-studies have been selected and analyzed by national and international literature. Results: Case studies were: 1. Florence Kelley’s research on insanitary working conditions among Sicilian home workers in Chicago (1899); 2. Death of forty-two Italian women in the Triangle Shirtwaist Factory fire in New York and the claim of Anna Gullo in the trial against the employers; 3. The report on the condition of Italian migrant women in the USA by Irene de Bonis dei Baroni de Nobili and the Women’s Trade Union League (1911); 4. The Maggia sisters Amelia, Quinta and Albina and the trial for compensation of radium related diseases (1928); 5. The contribution of Italian migrant Geraldina “Jennie” Sirchio to the T-room experiment at the Hawthorne Works in Chicago (1928). Conclusions: Italian migrant women, among others, played an important role in the USA social and economic development. Women were particularly exposed to infectious disease, fire risk, radium painting, repetitiveness, etc. Important trials, inquiries and legislation together with recognition of occupational diseases were fostered thanks to their often unknown sacrifice. Today as yesterday migrant workers should be valued and prevention improved.